Współczesne nazwiska rosyjskie pochodzenia polskiego - Marian Wójtowicz (Studia Rossica Posnaniensia)
The article presents an analysis of 349 surnames obtained from Russian telephone directories. The author discusses the most important phonetic and morphological features of Russian surnames of Polish origin, identifies their types and draws up a list of 116 most frequently used surnames.